Perancangan Sistem Informasi Penerimaan Peserta Magang Berbasis Web pada Kantor BPS Kabupaten Simalungun - Purba, Rizki Ikhwansyah; Samsudin, Samsudin (Teknik Informatika Fakultas Ilmu Komputer, 2024)
Designing an information system for accepting apprentices at the Simalungun Regency BPS office, the Simalungun Regency government is carrying out an internship program to develop skills and improve the quality of the local workforce. As an effort to increase efficiency and effectiveness in accepting apprentices. Acceptance of apprentices at BPS Simalungun Regency will have the main function of managing apprentice data, conducting data searches, sorting prospective apprentices, producing statistical reports, and sending notifications to apprentices. This system meets data security standards and limited access to authorized users. At the implementation stage, this system will validate data input for apprentices to avoid entering data that does not match the desired format, and also has a feature to delete data for apprentices who are inactive or not verified by BPS Simalungun Regency. Increases efficiency and effectiveness in accepting apprentices, streamlines the data verification process.